Improved Cementitious Tile Adhesives’ Workability and Mechanical Performance with the Use of Recycled Materials - Ana Lourenço; Luís Silva; Vera Fernandes; Pedro Sequeira (Infrastructures, 2022)
The impact that construction has on sustainability as a relevant consumer of materials is well known, especially with regard to cement, which contributes to high CO2 emissions. It is well known that in tile adhesives, cement add positive technical contributes, supporting tensile adhesion, especially after water immersion and freeze–thaw cycles. On the other hand, it is also known that that it is possible to replace Portland cement with alternative sources, such as blast furnace slag, fly and bottom ashes, or other pozzolanic materials. Even so, other materials can be also used to contribute to additional performance. This work intends to prove that using recycled materials or by-products is not just a potential way to replace existing materials, improving environmental sustainability, but also contributes additional value to mortars, such as cement-based tile adhesives. Different recycled waste materials are introduced to a cement-based tile adhesive and the evaluation of properties according to EN 12004 is conducted. The results show how the introduction of recycled rubber can contribute to improve the workability of a tile adhesive, acting as a lightweight aggregate. Moreover, it can contribute to reducing the dynamic elasticity modulus; thus, it has a potential contribution to reduce global tensions in tiling systems, and the adhesion results are maintained by the introduction of slag, another recycled material. The weight reduction reduces mortar consumption, one of the main targets to support indicated strategy and justify a more sustainable performance. The results indicate that the introduction of rubber and slag provide good technical and mechanical performance for the mortars, as well as excellent workability.